Pengaruh Metode Brainstorming terhadap Kemampuan Berpikir Kritis Siswa Kelas V di SD Inpres Bumi Sagu - Sandra Putri Wahyunisa; Mufidah Mufidah; Akina Akina; Nurul Kami Sani (Universitas Islam Sultan Agung, 2023)
The ability to think critically about students in Indonesia is relatively low, this is evidenced in the results of the 2018 PISA research survey. Selection of methods is needed to overcome these problems. This study aims to determine the effect of using the Brainstorming method on students' critical thinking skills in fifth grade mathematics at SD Inpres Bumi Sagu. The research design used the One-Group Pretest-Posttest Design with a sample of 18 students in class V B at SD Inpres Bumi Sagu. Data collection used multiple choice questions which included indicators of critical thinking with data analysis using the Paired Sample T-test assisted by the SPSS version 16 program. The results showed an increase in the indicators of knowing and solving problems 47.22; indicators analyze 33.33; indicators evaluate 30.55; and the indicators conclude 18.51. Based on the results of the t-test using the Paired Sample T-test, a sig. (2-tailed) value of 0.000 < 0.05 was obtained. Then the Ha hypothesis is accepted and Ho is rejected, meaning that the brainstorming method in mathematics subject matter of geometric shapes has an effect on the critical thinking skills of fifth grade students of SD Inpres Bumi Sagu.